Effect of vegetable oils on fatty acid composition and cholesterol content of chicken frankfurters - Belichovska Daniela, Pejkovski Zlatko, Belichovska Katerina, Uzunoska Zora, Silovska-Nikolova Aleksandra (IOP Publishing, 2017)
To study the effect of pork adipose tissue substitution with vegetable oils in chicken frankfurters, six frankfurter formulations were produced: control; with pork backfat; with olive oil; with rapeseed oil; with sunflower oil; with palm oil, and; with a mixture of 12% rapeseed oil and 8% palm oil. Fatty acid composition and cholesterol content and some oxides thereof were determined in the final products. The use of vegetable oils resulted in improvement of the fatty acid composition and nutritional of frankfurters. Frankfurters with vegetable oils contained significantly less cholesterol and some of its oxides, compared to the frankfurters with pork fat. The formulation with palm oil had the least favourable fatty acid composition. The use of 12% rapeseed oil improved the ratio of fatty acids in frankfurters with a mixture of rapeseed and palm oils. Complete pork fat replacement with vegetable oils in chicken frankfurter production is technologically possible. The mixture of 12% rapeseed oil and 8% palm oil is a good alternative to pork fat from health aspects. Further research is needed to find the most appropriate mixture of vegetable oils, which will produce frankfurters with good sensory characteristics, a more desirable fatty acid ratio and high nutritional value.